2014
DOI: 10.1097/jcn.0b013e31829c1414
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Services in Low- and Middle-Income Countries

Abstract: Although patients similarly benefit from CR, few programs are available in LMICs. Policies need to be implemented to increase provision of tailored CR models at the global and national level, with evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…While the availability of CR programs in the majority of Latin American countries is just beginning to be known, their broader implementation is hampered by lack of evidence demonstrating benefits in these lower-resource settings 12 . A recent review of randomized controlled trials (RCTs) of CR in LMICs identified only two RCTs, neither of which was undertaken in Latin America 13 . To support broader CR delivery and service reimbursement, we must robustly demonstrate that CR is beneficial in this context.…”
Section: Introductionmentioning
confidence: 99%
“…While the availability of CR programs in the majority of Latin American countries is just beginning to be known, their broader implementation is hampered by lack of evidence demonstrating benefits in these lower-resource settings 12 . A recent review of randomized controlled trials (RCTs) of CR in LMICs identified only two RCTs, neither of which was undertaken in Latin America 13 . To support broader CR delivery and service reimbursement, we must robustly demonstrate that CR is beneficial in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil was chosen as the LMIC for testing because of: (1) the great burden of CVD, 10 (2) the availability of country-specific CR guidelines10 11 (there are few national CR guidelines developed in LMICs) and (3) no RCT of CR (with any outcome) in South America to our knowledge 5…”
Section: Methodsmentioning
confidence: 99%
“…Of the 103 middle-income countries globally, this search revealed CR services exist in 29 (28.2%) countries (Figure 1). These were: Algeria, 70 Argentina,42 Belarus, 69 Bosnia And Herzegovina, 69 Brazil, 68 Bulgaria, 69 China, 71 Colombia, 68 Costa Rica, 69 Cuba, 69 Ecuador, 42 Egypt, 72 India, 73 Indonesia, 74 Iran, 75 Malaysia, 69 Mexico, 68 Pakistan, 76 Panama, 69 Paraguay, 42 Peru, 68 Philippines, 43 Romania, 77 South Africa, 78 Sri Lanka, 69 Thailand, 69 Tunisia, 79 Turkey, 80 and Venzuela. 42 …”
Section: Cr Availability In Middle-income Countriesmentioning
confidence: 99%